Optogenetic elevation of postsynaptic cGMP in the hippocampal dentate gyrus enhances LTP and modifies mouse behaviors - Jelena Borovac; Jelena Borovac; Jelena Borovac; Jayant Rai; Jayant Rai; Megan Valencia; Megan Valencia; Hang Li; John Georgiou; Graham L. Collingridge; Graham L. Collingridge; Graham L. Collingridge; et al. (Frontiers in Molecular Neuroscience)
A major intracellular messenger implicated in synaptic plasticity and cognitive functions both in health and disease is cyclic GMP (cGMP). Utilizing a photoactivatable guanylyl cyclase (BlgC) actuator to increase cGMP in dentate granule neurons of the hippocampus by light, we studied the effects of spatiotemporal cGMP elevations in synaptic and cognitive functions. At medial perforant path to dentate gyrus (MPP-DG) synapses, we found enhanced long-term potentiation (LTP) of synaptic responses when postsynaptic cGMP was elevated during the induction period. Basal synaptic transmission and the paired-pulse ratio were unaffected, suggesting the cGMP effect on LTP was postsynaptic in origin. In behaving mice implanted with a fiber optic and wireless LED device, their performance following DG photoactivation (5–10 min) was studied in a variety of behavioral tasks. There were enhancements in reference memory and social behavior within tens of minutes following DG BlgC photoactivation, and with time (hours), an anxiogenic effect developed. Thus, postsynaptic cGMP elevations, specifically in the DG and specifically during conditions that evoke synaptic plasticity or during experience, are able to rapidly modify synaptic strength and behavioral responses, respectively. The optogenetics technology and new roles for cGMP in the DG may have applications in brain disorders that are impacted by dysregulated cGMP signaling, such as Alzheimer’s disease.